Doing away with the 'native speaker': a complex adaptive systems approach to L2 phonological attainment. Issue 4 (2nd October 2017) - Aslan, Erhan
Abstract : Employing the complex adaptive systems (CAS) model, the present case study provides a self-report description of the attitudes, perceptions and experiences of an advanced adult L2 English learner with respect to his L2 phonological attainment. CAS is predicated on the notion that an individual's cognitive processes are intricately related to his or her experiences in particular social contexts and all language activities are dynamically regulated. In the study, interview data and reflective essay entries were analysed. The findings revealed that motives for L2 speech production and the concomitant attempts to improve L2 phonology were in a phase transition between idiolect (individual) and communal (social) levels. Autonomy, experience and environment were influential in the reorganisation of the learner's attitudes and perceptions about L2 pronunciation and accent. In addition, the learner's awareness of phonological variation, external motives and individual goals interact with one another in a dynamic fashion. The learner appreciates linguistic diversity and rejects the idealised 'native speaker' norm in the acquisition of L2 phonology. Finally, based on the findings of the study, implications pertaining to L2 learning, teaching and research are discussed.